2D layered SiC/C2N van der Waals type-II heterostructure: a visible-light-driven photocatalyst for water splitting. (1st September 2020) - Xu, Liang; Ma, Zongle; Li, Quan; Chen, Tong; Peng, Bojun; Zeng, Jian; Zhang, Yingbin; Luo, Kai-Wu; Wang, Ling-Ling; Shuai, Cijun
Abstract : 2D layered SiC/C2 N type-II heterostructure is an effective photocatalyst for hydrogen production from water splitting by visible light. Abstract : Exploring simple, efficient and low cost photocatalysts for hydrogen production driven by visible light is a hot topic in the field of photocatalysis. Here, we study a two-dimensional (2D) layered SiC/C2 N van der Waals heterostructure as a possible visible light photocatalyst for water splitting, using hybrid density functional theory calculations. We find that the heterostructure composed of SiC and C2 N is a type II heterostructure with a mild band gap (1.58 eV), which can promote the effective separation of electron–hole pairs, thereby suppressing the recombination of photogenerated carriers. The phonon dispersion and ab initio molecular dynamics analysis indicate its good kinetic and thermodynamic stability. Remarkably, atomic projection density of states and energy band structure show that the valence band maximum (VBM) and conduction band minimum (CBM) of the SiC/C2 N heterostructure are provided by SiC and C2 N, respectively. And its band edge meets the requirements of the redox potential for water splitting. In addition, as the SiC-based heterostructure can retain the excellent visible light performance of the C2 N component, it laid the foundation for designing visible-light-driven SiC/C2 N photocatalysts. This work may provide valuable information for experimenters to design type II heterostructure photocatalytic materials for water splitting.